2 - VIEWPOINTS AND THE SUZUKI METHOD - A LECTURE BY DONNIE MATHER - Mather, Donnie; Tornaghi, Transcription by Isabel (O Percevejo Online, 2011)
This lecture, presented at the opening of the 2nd Engrupedança conference at UNIRIO, Rio de Janeiro in 2009, reviews the main points of the Viewpoints training method, as seen through the personal experience of actor Donnie Mather with SITI Company, directed by Anne Bogart. The text lists the content of the different viewpoints and describes the training, its applications and results through examples from various productions of SITI Company. Donnie Mather also introduces the Suzuki method which, according to him, complements the Viewpoints training.Keywords | Viewpoints | Suzuki method | SITI Company | Anne Bogart | training